IN VITRO EVALUATION OF THE FIBRINOLYTIC AND TOXICITY PROFILE OF A PROTEASE FROM STREPTOMYCES PARVULUS DPUA 1573 ISOLATED FROM AMAZONIAN LICHENS - Alencar, Viviane do Nascimento e Silva; Martins Barbosa Filho, José Pedro; Pedrosa Brandão Costa, Romero Marcos; Figueiredo Porto, Ana Lúcia; Lima Leite, Ana Cristina; Pajeu Nascimento, Thiago (Revista de Ciências Médicas e Biológicas, 2025)
Introduction: Thrombosis is one of the main causes of cardiovascular diseases, with blood clots being responsible for events such as acute myocardial infarction and stroke. Fibrinolytic enzymes, particularly those of microbial origin, have shown promise due to their effectiveness in degrading fibrin and their feasibility for large-scale production. Among them, the strain Streptomyces parvulus DPUA 1573, isolated from lichens in the Brazilian Amazon, demonstrated high fibrinolytic potential, drawing interest as a potential antithrombotic agent. Objective: To obtain and characterize a fibrinolytic enzyme from Streptomyces parvulus DPUA 1573 with potential use as an antithrombotic agent. Methods: The enzyme was produced by submerged fermentation, purified using an aqueous two-phase system, and evaluated through in vitro assays for thrombolytic, fibrinogenolytic, amidolytic, anticoagulant, cytotoxic, and hemolytic activities using human plasma, tumor cells, and erythrocytes. Results: The enzyme showed preferential partitioning of protease to the PEG-rich top phase. The crude extract and the pre-purified fibrinolytic protease exhibited thrombolytic degradation of 41.47% and 52.98%, respectively. Additionally, the protease displayed amidolytic activity through degradation of the Aα, Bβ, and γ chains of fibrinogen, being classified as a chymotrypsin-like serine protease. In vitro anticoagulant assays showed a slight prolongation of prothrombin time and partial thromboplastin time, with no effect on thrombin time. The enzyme also showed no hemolytic activity in the blood biocompatibility assay. Cytotoxicity testing against MDA-MB-231 and J774.A1 cells demonstrated 80% cell viability. Conclusion: These findings suggest that the fibrinolytic enzyme from Streptomyces parvulus DPUA 1573 holds potential for the development of a novel antithrombotic drug candidate..